2018
DOI: 10.4018/ijissc.2018040104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Accessibility of Computer Laboratories, Libraries, and Websites in Jordanian Universities and Colleges

Abstract: This article evaluates the accessibility computer laboratories, libraries, and web sites of five different institutions of higher education in Jordan. The evaluation is performed using a questionnaire and by expert visiting these institutions of higher education to check their accessibility according to a set of universal standard collected from the literature. The analysis of the results revealed a serious weakness in understanding, adopting and implementing web accessibility guidelines throughout nearly all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that cyberloafing is associated with reduced classroom attention (Taneja et al, 2015), low academic engagement (Ravizza et al, 2014), instructor-student conflict (Hembrooke & Gay, 2003) and poor academic performance (Dursun et al, 2018;Flanigan and Babchuk, 2015;Ravizza et al, 2014). Additionally, cyberloafing contributes greatly to the development of smartphone addiction among students (Doush and Alhami, 2018;Gokcearslan et al, 2016;Nwakaego and Angela, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported that cyberloafing is associated with reduced classroom attention (Taneja et al, 2015), low academic engagement (Ravizza et al, 2014), instructor-student conflict (Hembrooke & Gay, 2003) and poor academic performance (Dursun et al, 2018;Flanigan and Babchuk, 2015;Ravizza et al, 2014). Additionally, cyberloafing contributes greatly to the development of smartphone addiction among students (Doush and Alhami, 2018;Gokcearslan et al, 2016;Nwakaego and Angela, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Prior research has indicated that cyberloafing is linked to diminished classroom focus [ 15 ], decreased academic involvement [ 16 ], conflicts between instructors and students [ 17 ], and subpar academic achievement [ 16 , 18 , 19 ]. Furthermore, it has been observed that cyberloafing plays a significant role in the emergence of smartphone addiction among student populations [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Web accessibility guidelines outline the requirements that must be met in order to facilitate accessible information resources for diverse users, including people who are blind, visually impaired, deaf, hearing impaired, motor impaired, and more [ 26 , 35 ]. Among the most recognized standard accessibility guidelines is the W3C WCAG [ 21 ].…”
Section: Introductionmentioning
confidence: 99%